A computational model of politicians?bureaucracy relationship in a competitively authoritarian environment. (8th June 2011) - Lskavyan, Vahe; Melkonian, Vardges
We develop a model that captures the basic characteristics of competitively authoritarian regimes. An incumbent (government) faces a challenge from a rival (opposition). There is also an agent (bureaucracy) who can shirk and can interfere in this contest. Shirking is costly to the incumbent. The contestants offer the agent contingent pay-offs that determine the agent's optimal strategy. This, in turn, determines each contestant's winning probability. We calculate this probability for every possible strategy combination of the contestants. The result is a two-player (incumbent?rival)zero sum game. We compute Nash Equilibria for several interesting scenarios and find that equilibria can exist where the incumbent deliberately encourages bureaucratic shirking (corruption) in exchange for loyalty. More generally, the incumbent's incentive to encourage shirking can depend on public dissatisfaction with shirking, the bureaucracy's electoral influence, the opposition's strength and the asymmetry in the contestants' ability to impose punishments on the bureaucrats.